Congenital Hydrocephalic Monster in an Indigenous Gir Calf: A Case Report - Borakhatariya, Devasee N; Raval, Rupesh J; Vala, Karsan B; Chavda, Bakti P; Prajapati, Sanny G (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
There are several types of fetal dropsy (fetal ascites, fetal anasarca, fetal hydrocephalus), which have obstetrical importance  preventing normal easy delivery of calf. Hydrocephalus is  one of the fetal causes of dystocia. It is characterized by an  accumulation of fluid which may be in the ventricular system  or between the brain and the subarachnoid space. The swelling  or enlargement of cranium occurs as a result of an imbalance  between formation and drainage of cerebrospinal fluid (Arthur  et al., 2001). This congenital dropsical condition is associated  with an autosomal recessive gene, whereas some cases are due  to BVD-MD or bluetongue virus infection in bovine (Roberts,  1986). Though this dropsical condition is rare in Gir cattle, it  is reported in many other species (Dhami et al., 2007; Kumar  et al., 2010; Parmar et al., 2018). The present case report depicts  an unusual instance of hydrocephalic monster in an indigenous  Gir calf, causing dystocia, which was successfully managed by  per vaginum.
Keywords: Congenital Hydrocephalic Monster; Indigenous Gir Calf; hydrocephalus